Virtual components design and reuse. - Seepold, Ralf, ....-; Martinez Madrid, Natividad, ....- (Boston : Kluwer Academic, 2001)
Design reuse is not just a topic of research but a real industrial necessity in the microelectronic domain and thus driving the competitiveness of relevant areas like for example telecommunication or automotive. Most companies have already dedicated a department or a central unit that transfer design reuse into reality. All main EDA conferences include a track to the topic, and even specific conferences have been established in this area, both in the USA and in Europe. Virtual Components Design and Reuse presents a selection of articles giving a mature and consolidated perspective to design reuse from different points of view. The authors stem from all relevant areas: research and academia, IP providers, EDA vendors and industry. Some classical topics in design reuse, like specification and generation of components, IP retrieval and cataloguing or interface customisation, are revisited and discussed in depth. Moreover, new hot topics are presented, among them IP quality, platform-based reuse, software IP, IP security, business models for design reuse, and major initiatives like the MEDEA EDA Roadmap.